Clinical relevance of retinal structure in children with laser‐treated retinopathy of prematurity versus controls – using optical coherence tomography. Issue 2 (19th September 2017) - Stoica, Florina; Chirita‐Emandi, Adela; Andreescu, Nicoleta; Stanciu, Alina; Zimbru, Cristian G.; Puiu, Maria
Abstract: Purpose: We aimed to assess the macular anatomy using spectral domain optical coherence tomography (SD‐OCT), in children born preterm who had laser‐treated retinopathy of prematurity (ROP), and to investigate the relationship between structural changes in macula and visual function. Methods: Thirty‐seven 3–8 years old children were included in the study in two groups: 20 children born preterm [(<34 weeks of gestation, birthweight (BW) <2000 g)] who had laser‐treated ROP in the Neonatology Department, Municipal Clinical Emergency Hospital of Timisoara, Romania; and 17 controls (children born at term, without eye disease, matched for age and gender). Spectral domain optical coherence tomography (SD‐OCT) imaging (Spectralis OCT) was performed at central fovea and 1 mm nasally. Results: In the ROP group (total 34 eyes), we included both eyes in 14 children, and on one eye in six other children. In the control group, both eyes for all 17 children were included. Central fovea thickness (CFT) was significantly higher in children born preterm and with laser‐treated ROP as compared to controls (275 ± 34.8  μ m versus 224 ± 27.2  μ m; p < 0.001). The laser‐treated eyes with ROP had mean best‐corrected visual acuity (BCVA) = 0.19 logMAR (20/31 Snellen); 35% had BCVA ≥0.3 logMAR (20/40 Snellen). In receiver operating characteristic curve (ROC) analysis, with BCVA as static variable (category 0 = BCVA ≤0.3 logMAR), the CFT cut‐off was 257  μ m (sensitivity: 0.917; specificity: 0.661; area under the curve: 0.810, p = 0.001). Conclusion: Years after the laser intervention, central fovea was significantly thicker in ROP laser‐treated children born preterm when compared to controls. Central fovea thickness (CFT) correlated strongly and inversely with BW and gestational age (GA) at birth, while a CFT value above 257  μ m was suggestive for suboptimal visual acuity. The proposed cut‐off value needs to be validated in future larger studies.